The Influence of Service and Trust Attributes on Loyalty, Empirical Study of Barbershop Services in Surakarta - Syafikurrosyad, Banun; Setiawan, Anton Agus (Archives of Business Research, 2023)
Service sector enterprises rely on customer confidence, centering on the excellence of service extended to clients. In the face of intensifying market rivalry, entrepreneurs must consistently introduce fresh ideas. The barbershop sector, a venture pursued by males across generations, has proliferated across Indonesia. This research aims to ascertain and assess the effect of service attributes on royalty within barbershop services, as well as to comprehend and evaluate the influence of trust on loyalty towards barbershop services. The research methodology employed in this study is purposive sampling, conducted with specific predefined criteria for participant selection. Researchers used primary data obtained directly from 120 respondents through a questionnaire which then for data analysis techniques used hypothesis testing that had been formulated. The data utilized in this study is primary data. The research findings suggest that both service attributes and trust play a constructive role in fostering customer loyalty within the realm of barbershop services.